2019
DOI: 10.1128/aac.02142-18
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Interactions between the Hepatitis C Virus Inhibitors Elbasvir and Grazoprevir and HIV Protease Inhibitors Ritonavir, Atazanavir, Lopinavir, and Darunavir in Healthy Volunteers

Abstract: The combination of the hepatitis C virus (HCV) nonstructural protein 5A (NS5A) inhibitor elbasvir and the NS3/4A protease inhibitor grazoprevir is a potent, once-daily therapy indicated for the treatment of chronic HCV infection in individuals coinfected with human immunodeficiency virus (HIV). We explored the pharmacokinetic interactions of elbasvir and grazoprevir with ritonavir and ritonavir-boosted HIV protease inhibitors in three phase 1 trials. Drug-drug interaction trials with healthy participants were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Drug-drug interactions have been reported between EBR/GZR and certain antiretroviral therapies for HIV infection. Increased GZR exposure has been reported when EBR/GZR is coadministered in combination with the fixed-dose combination of elvitegravir/cobicistat/ tenofovir disoproxil fumarate/emtricitabine (25) or with the ritonavir-boosted protease inhibitors atazanavir, lopinavir, and darunavir (26,27). Ledipasvir and velpatasvir have pH-dependent solubility, and therefore concomitant use of agents that increase gastric pH, such as proton-pump inhibitors and histamine H2 receptor antagonists, can reduce their bioavailability (28).…”
Section: Discussionmentioning
confidence: 99%
“…Drug-drug interactions have been reported between EBR/GZR and certain antiretroviral therapies for HIV infection. Increased GZR exposure has been reported when EBR/GZR is coadministered in combination with the fixed-dose combination of elvitegravir/cobicistat/ tenofovir disoproxil fumarate/emtricitabine (25) or with the ritonavir-boosted protease inhibitors atazanavir, lopinavir, and darunavir (26,27). Ledipasvir and velpatasvir have pH-dependent solubility, and therefore concomitant use of agents that increase gastric pH, such as proton-pump inhibitors and histamine H2 receptor antagonists, can reduce their bioavailability (28).…”
Section: Discussionmentioning
confidence: 99%
“…38 A pharmacokinetic study of GZR and rifampin in healthy volunteers found a significant decrease in C 24h of GZR after multiple oral rifampin doses, likely due to CYP3A4/P-gp induction by rifampin. 40 Combination of multiple doses of rifampin and SOF/VEL also led to a significant decrease in both SOF and VEL AUC by 72% and 82%, respectively. 18 Likewise, VOX AUC decreased by 73% when given with multiple doses of rifampin.…”
Section: Anti-infectivesmentioning
confidence: 91%
“…3D, Methods ). For mice receiving synZiFTR-controlled anti-Her2 CAR T cells, GZV was dosed every day at 25 mg/kg for 14 days, either alone or in combination with lopinavir/ritonavir (LPV/RTV, 10 mg/kg), an antiretroviral drug cocktail known to increase GZV bioavailability ( 61 ). Importantly, GZV inducer combinations have no effect on cells on their own ( Fig.…”
Section: Mainmentioning
confidence: 99%